2018
DOI: 10.1093/cercor/bhy192
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Phosphodiesterase 2A Activity in the Pathophysiology of Fragile X Syndrome

Abstract: The fragile X mental retardation protein (FMRP) is an RNA-binding protein involved in translational regulation of mRNAs that play key roles in synaptic morphology and plasticity. The functional absence of FMRP causes the fragile X syndrome (FXS), the most common form of inherited intellectual disability and the most common monogenic cause of autism. No effective treatment is available for FXS. We recently identified the Phosphodiesterase 2A (Pde2a) mRNA as a prominent target of FMRP. PDE2A enzymatic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 64 publications
7
58
0
Order By: Relevance
“…Indeed, several mRNAs encoding components of cAMP signaling cascade are target of FMRP (Darnell et al, 2011 ) among which, as above discussed, PDE2A is a major FMRP target (Maurin et al, 2018a ). Importantly, very recent data demonstrate that PDE2A is overactivated in Fmr1 KO mouse brain, leading to reduced cAMP levels, and pharmacological inhibition of PDE2A reverses exaggerated mGluR-LTD in Fmr1 KO hippocampus (Maurin et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several mRNAs encoding components of cAMP signaling cascade are target of FMRP (Darnell et al, 2011 ) among which, as above discussed, PDE2A is a major FMRP target (Maurin et al, 2018a ). Importantly, very recent data demonstrate that PDE2A is overactivated in Fmr1 KO mouse brain, leading to reduced cAMP levels, and pharmacological inhibition of PDE2A reverses exaggerated mGluR-LTD in Fmr1 KO hippocampus (Maurin et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…6 PDE2A was also recently shown to play a role in the physiopathology of fragile X mental retardation syndrome (FXS), and its pharmacological inhibition was proposed as a potential therapeutic approach for FXS. 7 This suggests that PDE2A gain of function would lead to intellectual disability (ID). On the other hand, a homozygous loss-of-function mutation in PDE2A (c.1439A>G; p.Asp480Gly) was recently associated with a early-onset hereditary choreapredominant movement disorder that is also associated with ID.…”
Section: P D E 2 a I N A F A M I L Y W I T H A T Y P I C A Lmentioning
confidence: 99%
“…This indicates an age-dependent and compartmentalized alteration of cAMP enzymes in FXS, suggesting tailored therapeutic approaches. Interestingly, it is found that treatment with PDE2 inhibitor BAY607550 rescues social deficits in infant (postnatal day 10-14) and adolescent (postnatal day 30) Fmr1 KO animals 32 . Although PDE4D expression has not been compared between normal and FXS samples, chronic treatment with PDE4D negative allosteric modulator (NAM) BPN14770 improves behavioral symptoms associated with social interaction and perseveration 44 .…”
Section: Discussionmentioning
confidence: 99%